Epstein-Barr virus infections - avidity test for IgG antibodies - Strašek, Katja (Zdravniški vestnik, 2001)
Background. We wish to introduce specific IgG avidity test as a supplementary assay in serological screening for Epstein-Barr virus infection if the status of patient cannot be resolved from a single serum sample with routine testing.Methods. Avidity of IgG antibodies was determined in sera of 57 patients with different stage of Epstein-Barr virus infection. Enzyme-immunoassay was used with a short incubation of G-molar urea included in the procedure. Urea should remove low avtdity antibodies. Avidity was expressed as the avidity index: Avidity testing with commercial kit was done as well Results. Low avidity index was found for IgG antibodies of acute phasesera and high for those of past infection, recent infection and reactivation of endogenic virus. Conclusions. Avidity test for IgG antibodies might be supplementary assay toprove acute infection but also to resolve some other clinical states related to Epstein-Barr virus.
Keywords: Antibodies, viral; Antibody affinity; diagnostika; Herpesvirus 4, human; IgG; protitelesa; virus Epstein-Barr